The Role of Social Media in the Evolution of the Arabic Language Among the Younger Generation - Muhammad Fadhil Uzmi; Muhammad Miftah Al-Khalili; Muhammad Rifqi Fauzi; Sahkholid Nasution (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research explores the role of social media in modern society and its impact on communication, especially in learning Arabic and the evolution of Arabic language structure. Social media functions as an effective and easy-to-use communication tool, enabling the wide dissemination of news and information. According to Andreas K. & Michel H., social media enables the creation and exchange of user-generated content, in various forms such as social networks, virtual game worlds, and forum services. Advances in technology and information have expanded internet access, especially among the younger generation, which has the potential to provide positive benefits in interacting and learning. However, social media use also carries risks such as crime and violence. Therefore, it is important to use social media wisely and responsibly. This research uses library research methods with constant comparative and content analysis techniques to collect and analyze data from various relevant literature. In learning Arabic, audio media is an important tool that conveys messages through sound, both orally and in writing. Animation-based audio media can increase motivation and enthusiasm for learning. In addition, this research also highlights changes in the structure of the Arabic language from Fusha to Amiyyah, which are influenced by foreign languages and practical adaptations in everyday communication. Egyptian Arabic (Amiyyah) exhibits distinct phonological characteristics, such as terminating final vowels and weakening of the article